Artes visuais na proposta curricular do estado de São Paulo: Portinari ausente - Assumpção, Flaviana Christine Vallim Peres Marques (2010)
This Project starts from an observation and a questioning: why haven t Cândido Portinari s works - greatest Brazilian painter and born in the state of São Paulo -, been taken into account by the Curricular Proposal of the State of São Paulo regarding the Arts teaching books, in particular the visual ones? Doesn t his work have any importance for the country? Don t the elaborators of the mentioned proposal know him? From the analysis of this material, a research has been done with the survey of bibliographies about the painter that could reveal his life, not only the one already known of the general public, but the one that could serve as a basis to teachers that teach art in public schools of the state of São Paulo. Through this investigation, we try to show someone worried about his people, an educator made by the image and a man formed by the observation of his work. The first chapter reveals us Portinari s formation, his family, religiosity, his involvement with Communism, his friends, his stay in Europe, his moving to Rio and his occasional trips to Brodósqui; besides the awards received, his escape of school and the greatness of his work. The second chapter shows the reader all the educational features of this painter, his concerns about the future of education in the country and mainly about the simple man who has been building this nation and not revealed by our old masters. Which man does Portinari show in his works? The third chapter compares and analyzes contemporaneous artists works taken into account by the Curricular Proposal of the State of São Paulo. It inquires about the presence of these education icons and reflects/questions Cândido Portinari s absence.